Adipose Tissue–Preserved Skin Graft: Applicability and Long-Term Results. Issue 3 (September 2017) - Chung, Bryan; O'Mahony, Gavin D.; Lam, Gretl; Chiu, David T. W.
Abstract : Background: Composite grafts consisting of adipose tissue and skin have been reported in the literature but have been restricted to areas smaller than 4 to 5 cm 2 . The senior author (D.T.W.C.) has developed a technique of adipose tissue–preserved full-thickness skin grafts for larger areas with success similar to that achieved with conventional full-thickness skin grafts. Methods: All cases of the senior author involving a full-thickness skin graft were identified and reviewed to identify cases in which adipose tissue–preserved full-thickness skin grafts were used. Indication for skin grafting, anatomical location of recipient and donor sites, size of graft, total number of grafts received by each patient, and percentage take were extracted from patient charts. Graft take was measured between days 5 and 14. Results: A total of 72 adipose tissue–preserved skin grafts on 47 patients were identified from 1994 to 2009, with a median follow-up of 8 years. The size of defect ranged from 0.7 to 210 cm 2, with a median area of 6 cm 2 (interquartile range, 2.5 to 15 cm 2 ). Only six of 72 grafts were found to have less than 100 percent take. The lowest take percentage was 85 percent in a graft with an area of 2.6 cm 2 . There were no graft failures. Conclusions: This study confirms the proof-of-concept that both larger and distant donor- site adipose tissue–preserved skin grafts are a viable alternative to conventional defatted full-thickness skin grafting. It appears that there is a low complication rate with respect to graft failure or incomplete graft take. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.